Strategic Planning Of Hospitality Information Systems Using The Ward And Peppard Approach Case Study At Buleud Villa, Garut District - Elin Rosliani; Dinar Rahayu (Institut Pendidikan Indonesia, 2022)
Hospitality is one area that has the potential to implement information systems because hospitality is a business that prioritizes satisfaction, in this case, namely service. A good business strategy is needed to support the business. Talking about business strategy will not be separated from the so-called strategy of information systems and information technology. Therefore, a mature information system strategic planning can be used as a reference to gain a competitive advantage for Villa Buleud Garut.The purpose of this study is to analyze environmental factors to determine the strengths, weaknesses, opportunities and threats that are owned and to identify the critical success factors so that a proposed information system strategy plan can be developed in the form of an application development portfolio at the future Villa Buleud.In this study the authors made direct observations at Villa Buleud, conducted interviews, and gave questionnaires to related parties and read literature. In compiling the framework in this study the authors used the Ward and Peppard approach. Which of these approaches is to carry out an analysis of the Internal Business Environment, External Business Environment, Internal IS/IT Environment, and External IS/IT Environment using several analytical methods, namely Value Chain analysis, PEST Analysis, Five Force Porter, McFarlan Strategic Grid, SWOT Analysis, Critical Success Factor, and Balanced Scorecard. The final result of this research is the proposed formulation of the future IS/IT strategy for Villa Buleud Garut which includes changes to the vision and mission of Villa Buleud, changes to organizational structure, information system application requirements, network architecture, future business processes, and future Villa Buleud application portfolio.Keywords: Information Systems and Information Technology Strategy, Ward and Peppard, Value Chain analysis, PEST Analysis, Porter's Five Forces, McFarlan Strategic Grid, SWOT Analysis, Critical Success Factor, Balanced Scorecard, and application portfolio.